Puzzle Game With a Combination of Forward Chaining and Backward Chaining Methods - Jonson Manurung Manurung (Jurnal Info Sains : Informatika dan Sains, 2020)
This research discusses how to find a solution in the secret code puzzle game. Because the author sees a fairly difficult solution in the game, a solution is needed to get the answer. In this secret code puzzle game, the writer uses four methods to find a solution, namely: Forward Chaining and Backward Chaining. The purpose of this final project is to create software to find a secret code puzzle game solution that we usually play in IQ test games. Explain how the four methods used by the author to find a solution work and also compare the speed of the four methods used to find out which method is the fastest. The results achieved are the authors make software in order to determine which method is the fastest and which method is late in solving the questions provided so that the author can find out which method is suitable for finding solutions in the secret code puzzle game and also the author succeeded in making the game. The secret code puzzle becomes a computer game